The effect of CSR and other determinants on shareholder value / Jevella Myrna Jelius - Jelius, Jevella Myrna (2019)
For any businesses, SMEs (Small and Medium Enterprises) to large corporations, linking firms with Corporate Social Responsibilities (CSR) activities can bring different opinion among the managers and shareholders. Managers’ concern is to exercise their best effort in running the firms which can increase firms and shareholders’ value. This is in line with the shareholders’ goal which the purpose of their contribution is to make income. However, to some, CSR activities can be a burden for the shareholder since it is a costly project. The over-investment of managers in CSR activities may concern the shareholders earning. Agency theory is used as the underlying theory to further understand the concept of CSR among principle (board of directors) and agent (shareholders). This research aim to study the effect of CSR and other determinants on shareholder’s value. It specifically studies on the top 10 company in Malaysia based on the highest market capitalization that is listed in the Kuala Lumpur Stock Exchange. This research used secondary sources where the data obtained from annual report and sustainability report. The research suggested that there is a significant relationship between CSR and shareholder’s value. It is hope that the study can help in making investment decision for the investors.